Determinants of U.S. Business Investment - Kopp, Emanuel (Washington, D.C. : International Monetary Fund, 2018)
U.S. business investment has taken a serious toll during the global financial crisis and also in the recovery phase investment did not pick up as expected. What is surprising is that the alleged investment slowdown happened at a time of record corporate profits and retained earnings, highly supportive financial conditions, improved sentiment, rising equity valuations, and strong labor markets-factors established in supporting business investment. Applying accelerator models and Bayesian Model Averaging, this paper discusses the extent to which U.S. business investment has been unusual. Results suggest that cautious expectations of future aggregate demand growth explain most of the weakness in investment, and that the oil and gas sector accounts for a considerable portion of the investment slump. Consequently, the behavior of U.S. business investment in recent years has not been unusual once these factors are taken into account. Also, there is very little evidence for uncertainty holding back investment, or that firms' financial measures "crowded out" capital expenditure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet